Deliver Anti-inflammatory Drug Baicalein to Macrophages by Using a Crystallization Strategy - Zhang, Jianming; Teng, Chao; Li, Caolong; He, Wei (Frontiers in Chemistry, 2020)
Macrophages are potent to modulate inflammation via phenotypic switch and production of inflammatory factors. Baicalein (BCL) is frequently used to alleviate inflammation; however, its application is always hindered due to low solubility. Herein, BCL nanocrystals (BNRs) were prepared to improve its delivery to macrophages. The prepared BNRs have a diameter of 150 nm with a rodlike structure. The nanocrystals could be well taken up by macrophages via caveolar pathway and, therefore, promote the polarization switch from proinflammatory phenotype to anti-inflammatory macrophages, and alleviate the inflammation via reducing production cytokine IL-12. In conclusion, crystallization strategy is promising to improve the solubility of BCL and promote its antiinflammatory activities.